Perancangan dan Analisis Kinerja Pompa Sentrifugal dengan Konfigurasi Paralel dan Seri untuk Kebutuhan Laboratorium Teknik Mesin - Kunarto Kunarto; Farhan Alfarizi Azmi; Riza Muhida; Muhammad Riza; Indra Surya; Bambang Pratowo; Zein Muhamad; Harjono Saputro; Mulyana (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2026)
Centrifugal pumps are the main component in pumping systems that are widely applied in industry, agriculture, and practical activities in engineering laboratories. This study aims to design and build a centrifugal pump tester with single, series, and parallel configurations as a learning medium in the Mechanical Engineering Laboratory. This tool uses two National TRANS GP-125 pump units with a discharge specification of 30 L/minute and a power of 125 W. The research method includes the stages of design, fabrication, testing, and technical calculations including total head, major and minor pressure losses, and impeller dimension analysis. The test results show that the parallel configuration increases the discharge capacity, while the series configuration is superior in producing higher heads. The system efficiency reaches 69%, still within the standard range of pump efficiency (63–84%). This study produces interactive learning media that can help students understand the working principles of centrifugal pumps and the effect of system configuration on hydraulic performance.